TRANSMISI ETIKA KE TATANAN POLITIK PERSPEKTIF MUHAMMAD ABID AL-JABIRI - Burhanuddin, Nunu (ALQALAM, 2009)
Several political issues are presumed having a relationship with the ethical values such as the problems of authority and its distribution, the application of laws, human rights, women emancipation, social justice, the distribution of national wealth, economics justice, and etc. These problems show us the importance of ethical reference to polish the political countenance as well as to straighten up the political manoeuvres that are often full of intrigues, arrogance, and tyranny. The transmission concept from ethics to the political order that has ever been stated by Aristotle (384-322 B.C.) in his book “Politea” on political matters, and his “Nicomachean” on moral issues is presumed inspiring the philosophers both in the West and in the East. This article elaborates Muhammad 'Abid Al Jabiri's thought (1936-…), a Muslim thinker from Morocco who classifies ethical values that are transmitted into political order in the Muslim World consisting of four main variants; (1) subservience ethics, an ethical system that is inherited by Persian sultanate; (2) happiness ethics, an ethical system of Greece; (3) transitory ethics, an ethical system developed by Sufi order; and (4) Muru'ah ethics, an ethical system developed in the Arabian World. According to al-Jabiri, these all four systems still left the important matters dealing with the claim of progressive and futuristic -oriented human dynamics. Therefore, al-Jabiri proposed a recommendation for Arabian and Islamic world in order to exceed such ethical systems and to side with the pious deed ethics and profit that became their tendency.